2021
DOI: 10.1371/journal.pone.0256328
|View full text |Cite
|
Sign up to set email alerts
|

Identifying fungal-host associations in an amphibian host system

Abstract: Host-associated microbes can interact with macro-organisms in a number of ways that affect host health. Few studies of host-associated microbiomes, however, focus on fungi. In addition, it is difficult to discern whether a fungal organism found in or on an ectotherm host is associating with it in a durable, symbiotic interaction versus a transient one, and to what extent the habitat and host share microbes. We seek to identify these host-microbe interactions on an amphibian, the Colorado boreal toad (Anaxyrus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 85 publications
(129 reference statements)
1
11
0
Order By: Relevance
“…During the summer of 2019, we obtained skin swabs from a subalpine boreal toad site in Chaffee County, Colorado with an approved IACUC protocol (#2629) and an active Colorado Parks and Wildlife scientific collection permit (19HP0998). Since past research has shown the importance of life stage to skin mycobiome composition and diversity (Alexiev et al, 2021;Kueneman et al, 2016b), we sampled at least 3 individuals from each life stage (tadpole, metamorph, subadult, and adult). Individual boreal toads were captured by hand while wearing sterile nitrile gloves and swabbed 10 times using double-headed rayon-tipped swabs (BD BBL, East Rutherford, New Jersey) (n = 16 animals swabbed total).…”
Section: Field Collection and Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…During the summer of 2019, we obtained skin swabs from a subalpine boreal toad site in Chaffee County, Colorado with an approved IACUC protocol (#2629) and an active Colorado Parks and Wildlife scientific collection permit (19HP0998). Since past research has shown the importance of life stage to skin mycobiome composition and diversity (Alexiev et al, 2021;Kueneman et al, 2016b), we sampled at least 3 individuals from each life stage (tadpole, metamorph, subadult, and adult). Individual boreal toads were captured by hand while wearing sterile nitrile gloves and swabbed 10 times using double-headed rayon-tipped swabs (BD BBL, East Rutherford, New Jersey) (n = 16 animals swabbed total).…”
Section: Field Collection and Isolationmentioning
confidence: 99%
“…We selected representatives from 16 unique fungal isolates, which was a tractable number to work with given laboratory resources. We used previously published ITS marker gene sequences from a past research study of the boreal toad skin mycobiome (sequences are deposited at the European Nucleotide Archive (ENA) in association with the project accession PRJEB41738), which identified fungal OTU's that were associated with the host (at each distinct life stage) as opposed to its habitat (Alexiev et al, 2021). Although we cultured and sequenced 120 distinct isolates, we did not have the capacity to test each against Bd at the time, so we used our previous study results to choose a tractable number to test.…”
Section: Fungi Versus Bd Lawn Plate Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our work investigates how the J. lividum strain BTP, which is specifically found on this host, and other skin-associated bacteria interact with Bd on the Colorado boreal toad ( Anaxyrus boreas boreas ), which is a high-elevation wetland amphibian that is locally endangered in the Rocky Mountains due to Bd ( 41 44 ). Research on this species to date has prioritized the use of next-generation sequencing and in vivo treatments to develop an effective probiotic bioaugmentation strategy for boreal toads ( 12 , 34 , 35 , 45 47 ). Adapting probiotic treatments to field conditions in wild populations remains as ongoing work.…”
Section: Introductionmentioning
confidence: 99%